Discovering The Experience Of Recovering Clients Undergoing The 7 Steps Recovery In Addiction Program (7-sra) As An Aftercare Treatment - Mohamad Isa Amat; Muhammad Khairi Mahyuddin; Haslinda Mat Jais; Ku Suhaila Ku Johari; Saf utra Pamidi; Nurfarhah Mohd Najib (Centro de Investigaciones en Ciencias Sociales y Humanidades desde America Latina, 2024)
The high number of drug addiction and relapse rate cases among Muslim clients in Malaysia has been always imposing apprehension upon Malaysians. This underpins the fact that there are rooms for more treatment options from different dimensions to be developed as the complementary action to the existing ones. Recognizing the etiological factor of addiction is also epitomized from individual spirituality, the 7-Steps Recovery in Addiction (7-SRA) was initiated based on Islamic teaching to further addressing this issue through the self-purification and repentance (tazkiyyat al-nafs). An in depth qualitative case study research was conducted to discover the experiences of 8 recovering clients as the participants in an aftercare center to discover their experience undergone the 7 Step in Recovery in Addiction Module. The data was triangulated by using in-depth interviews, observation notes and document analyses. The findings revealed that there were two emerging themes from informants’ shared experiences (pre and post intervention) which were spiritual and behavioral dimensions. 7-SRA was reported to be helpful approach for the participants in recovery process; thus 7-SRA is relevant to be employed as an evident-based practice (EBP) in drug addiction problem in particular as an aftercare treatment.